Synthesis of (MeAla)TANDEM, the bis(N-methylalanine) analog of des-N-tetramethyltriostin A - Dhaon, Madhup K; Olsen, Richard K (Journal of organic chemistry, 1981)
(MeAla super(2), MeAla super(6))des-N)-Tetramethyltriostin A (3), an analogue of the bicyclic octadepsipeptide antibiotic triostin A (1), has been prepared. Analogue 3 is of interest in studies relating to the mode of binding of the triostin antibiotics to nucleic acids. The analogue contains N)-methyl-L-alanine units in place of the two normal L-alanines and lacks the four N)-methyl groups common to the two pair of cysteine and valine residues.